Biological activity of clovers – Free radical scavenging ability and antioxidant action of six Trifolium species. (October 2014) - Kolodziejczyk-Czepas, Joanna; Nowak, Pawel; Kowalska, Iwona; Stochmal, Anna
Abstract Context: Clovers were chosen on the basis of traditional medicine recommendations, agricultural value, or available information on their promising chemical profiles. Objective: This study evaluates and compares free radical scavenging and antioxidant properties of six clover species: Trifolium alexandrinum L. (Leguminosae), Trifolium fragiferum L., Trifolium hybridum L., Trifolium incarnatum L., Trifolium resupinatum var. majus Boiss., and Trifolium resupinatum var. resupinatum L. Materials and methods: Free radical scavenging activity of the extracts (1.5–50 µg/ml) was estimated by reduction of 1, 1-diphenyl-2-picrylhydrazyl (DPPH) and 2, 2′-azino-bis(3-ethylbenzthiazoline-6-sulphonic) acid (ABTS) radicals. The Trifolium extract effects on total antioxidant capacity of blood plasma were determined by the reduction of ABTS+ and DPPH radicals, as well as with the use of the ferric reducing ability of plasma (FRAP) assay. Results: The UPLC analysis of chemical profiles of the examined extracts showed the presence of three or four groups of phenolic substances, including phenolic acids, clovamides, isoflavones, and other flavonoids. The measurements of free radical scavenging and ferric reducing ability of the examined clover extracts revealed the strongest effect for T. alexandrinum. Furthermore, antioxidant activity assays in human plasma have shown protective effects of all extracts against peroxynitrite-induced reduction of total antioxidant capacity. Conclusions: Trifolium plants may be a rich source of bioactive substances with antioxidant properties. The examined extracts displayed free radical scavenging action and partly protected blood plasma against peroxynitrite-induced oxidative stress; however, the beneficial effects of T. alexandrinum and T. incarnatum seem to be slightly higher.